Exploration and Detection of sinkhole in Lahat, Perak with Emphasis on Electrical Resistivity - binti Jamaludin, Nur Farhana (Universiti Teknologi PETRONAS, 2016)
This project entitled Exploration and detection of sinkhole in Lahat, Perak with emphasis on electrical resistivity (ER) survey. The investigation of resistivity survey is commonly recommended by practicing non – seismic method to obtain the necessary data of subsurface lithology in terms of resistivity and conductivity. This research study aims at determining the lithology of subsurface and its content that filled the pore spaces if presence. The area of study is located in Lahat area which situated in Central Perak, Malaysia and also found lies within the Kinta Valley area. In general, through the regional study of Kinta Valley area, it is highly verified that the area is mainly composed of karst topography that represents in the form of limestone in many places lies within the Kinta Valley area. However, due to the time constraint, we unfortunately could not organise the first geological fieldwork as planned earlier in this semester. Essentially, the first fieldwork is accomplished to obtain the overview of the geological setting in the proposed location. Nevertheless, the author manages to discover a case study which was conducted at the area adjacent to the proposed location in this study. One of the outcrops is to be found in Kampung Pengkalan, Lahat, Perak, Malaysia that had been taken into consideration of more future research study to be conducted especially in sinkhole detection. This location was once 5 m depth of sinkhole happened in year of 2014 which at least caused the damage of three houses. This work provides the general trends expected in direct tests for exploration and detection of sinkhole formation beneath limestone rocks.